Just Rewards? Local Politics and Public Resource Allocation in South India - Besley, Timothy; Pande, Rohini; Rao, Vijayendra (Oxford University Press for the World Bank, 2013)
What factors determine the nature of political opportunism in local government in South India? To answer this question, we study two types of policy decisions that have been delegated to local politicians—beneficiary selection for transfer programs and the allocation of within-village public goods. Our data on village councils in South India show that, relative to other citizens, elected councillors are more likely to be selected as beneficiaries of a large transfer program. The chief councillor's village also obtains more public goods, relative to other villages. These findings can be interpreted using a simple model of the logic of political incentives in the context that we study.